PENGARUH PENERIMAAN PAJAK, PDB DAN DEFISIT ANGGARAN TERHADAP UTANG LUAR NEGERI INODNESIA 1997-2024 - Lathifah Aini; Indra Maipita (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Indonesia's external debt has experienced a sustained upward trajectory, rising from IDR 397 trillion in 1997 to IDR 6,800 trillion in 2024. This study examines the partial and simultaneous effects of tax revenue, Gross Domestic Product (GDP), and budget deficit on Indonesia's external debt using annual time series data spanning 1997–2024, comprising 28 observations sourced from the World Bank and the Ministry of Finance of the Republic of Indonesia. Multiple linear regression under Ordinary Least Squares (OLS) estimation via EViews 12 was employed as the analytical framework. Results indicate that tax revenue exerts a significant negative effect on external debt, confirming that stronger fiscal capacity reduces dependence on external borrowing. GDP shows a significant positive effect, reflecting that economic growth continues to be accompanied by disproportionate public expenditure expansion consistent with Wagner's Law. The budget deficit produces a significant negative coefficient, implying that Indonesia predominantly finances deficits through domestic instruments, particularly Government Securities. Collectively, the three variables account for 97.30 percent of the variation in Indonesia's external debt, underscoring the strategic imperative of tax reform and domestic capital market deepening as long-term fiscal independence strategies.